“Buddhist-Christian Style”: The Collaboration of Prip-Møller and Reichelt—From Longchang Si to Tao Fong Shan Christian Centre - Weiqiao Wang; Yan Liu (Religions, 2024)
Buddhist architecture plays a crucial role in traditional Chinese architecture, representing the localized adaptation of Buddhism, a foreign religion, in China. Historically, abundant materials, including paintings, photographs, and texts, demonstrate the longstanding interest of visiting Christian missionaries in Chinese Buddhist architecture. As their understanding deepens, Buddhist architecture becomes a valuable reference for the Sinicization of Christian venues in China. Unlike the “Chinese Roof with Western walls style” or “mixed Easten and Western façade style”, Tao Fong Shan represents a “Buddhist-Christian style”, with its success rooted in the similarity of life and spatial modes between Buddhist and Christian monasteries. Using Tao Fong Shan Christian Centre as a case study, this article examines the localization construction of Christian architecture. It explores how Norwegian missionary Karl Ludvig Reichelt (1877–1952) and Danish Christian architect Johannes Prip-Møller (1889–1943) collaborated to establish a Christian center targeting Buddhists. Through an in-depth study of Prip-Møller’s field research in the 1930s, especially his analysis of Longchang Si, the article investigates how Tao Fong Shan learned from it and transformed its spatial characteristics to achieve a localized sense of space perception through site selection, layout, and spatial design. It ultimately aims to influence the beliefs of Buddhists within the local context.